Trapped in Toyland - Stewart, Molly Mia.; Pascal, Francine; Hu, Ying-Hwa.; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1994)
Elizabeth and Jessica Wakefield are looking forward to a perfect Christmas Eve. They're going shopping in the biggest department store they've ever seen! And the fun really starts when they realize the store has closed--with them inside.
Keywords: Department stores -- Juvenile fiction; Young adult fiction